Pengembangan Sikap Anak Dengan Metode Diskusi,Motivasi dan Rutin Mengikuti Kegiatan Kerohanian - Vivo Mei Ester Tambunan; Randa Putra Kasea Sinaga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Attitude development is carried out in children in order to direct children to have good moral attitudes. Especially for children who are at the age of approaching maturity at the age of 11-15 years, because at that age children have thoughts in a mature direction. Attitude development in children this time was carried out by one of the students in making a mini project to solve one client's problem which was my responsibility in the PKL I course, and field work practice was carried out at the Child Welfare Institution. What is meant by Field Work Practice or abbreviated as PKL is the activity of implementing learning theories received in lectures to the field or directly in the community. With the aim of training students' abilities in the world of work. In making the PKL I mini project, it is carried out using the casework method using general stages, namely Engagement,Intake,Contract,Assessment,Planning,Intervention,Evaluation and Termination. The method used to solve client problems is to conduct discussions, motivate, and regularly participate in spiritual activities in the church. The purpose of doing this strategy is to develop children's attitudes towards a better direction.